Modular Print Materials: Philippine Way of Learning Delivery In Times Of New Normal - THELMA MANABAT (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Philippine educational system was designed for an era that no longer exists nowadays. This is true in the face of a fast-changing world that deeply revolutionized our young learner’s attitudes, values, and behavioral predilections. In like manner, parents and families are placed in a quandary as they are confronted with the mounting admixture of formal and informal learning options and opportunities for their children. A module is a unit of work in a course of instruction that is virtually self-contained and a method of teaching that is based on the building of skills and knowledge in discrete units. It is a form of a self-instructional package which is regarded as a relatively recent phenomenon. It enables the learner to have control over his learning and takes greater responsibility for his learning opportunity. The writer believes that modular print material is the most effective in optimizing the students’ academic performance or achievements in attaining the main objective of the subject.